Effectiveness and safety of femtosecond laser-assisted lens fragmentation and anterior capsulotomy versus the manual technique in cataract surgery - Reddy, Kasu Prasad; Kandulla, Jochen; Auffarth, Gerd U. (Journal of cataract and refractive surgery, 2013)
Purpose - To evaluate the effectiveness and safety of cataract surgery using femtosecond laser-assisted lens fragmentation and anterior capsulotomy versus manual cataract surgery. - Setting - MaxiVision Eye Hospital, Begumpet, Hyderabad, India. - Design - Randomized controlled open-label multisurgeon prospective trial. - Methods - Patients (at least 18 years old) were randomized to femtosecond laser-assisted lens prefragmentation and capsulotomy or manual capsulorhexis and standard phacoemulsification. Measured outcomes were effective phacoemulsification time (EPT), surgeon-assessed ease of phacoemulsification, mean phaco energy, mean phaco time, balanced salt solution volume, capsulotomy precision, and adverse event rates. - Results - Fifty-six eyes had the femtosecond laser procedure, and 63 had manual cataract surgery. The mean EPT was significantly lower in the laser group (5.2 seconds ± 5.7 [SD]) than in the manual group (7.7 ± 6.0 seconds) (P=.025). There was a significant difference in the mean phaco energy between the 2 groups (13.8% ± 10.3% in laser group; 20.3% ± 8.1% in manual group) (P<.001). There were no significant between-group differences in the ease of phacoemulsification, mean phaco time, or balanced salt solution volume. Laser-assisted capsulotomies were significantly more accurate and precise (intended diameter, circularity, centration) (P<.01). The safety profiles of the procedures were equivalent, with no adverse events at the 1-day follow-up. - Conclusion - The femtosecond laser platform was effective and safe in cataract surgery, reducing EPT and the mean phaco energy during lens fragmentation and providing precise and reproducible capsulotomies. - Financial Disclosure - Dr. Reddy has received travel and research grants from Technolas Perfect Vision GmbH, Dr. Kandulla is an employee of Technolas Perfect Vision GmbH (a Bausch & Lomb company), and Dr. Auffarth has received travel and research grants as well as lecture fees from Technolas Perfect Vision GmbH/Bausch & Lomb.
Gesehen am 17.12.2021